If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(-3+8n)-6n=4n+5(5n+4)
We move all terms to the left:
5(-3+8n)-6n-(4n+5(5n+4))=0
We add all the numbers together, and all the variables
5(8n-3)-6n-(4n+5(5n+4))=0
We add all the numbers together, and all the variables
-6n+5(8n-3)-(4n+5(5n+4))=0
We multiply parentheses
-6n+40n-(4n+5(5n+4))-15=0
We calculate terms in parentheses: -(4n+5(5n+4)), so:We add all the numbers together, and all the variables
4n+5(5n+4)
We multiply parentheses
4n+25n+20
We add all the numbers together, and all the variables
29n+20
Back to the equation:
-(29n+20)
34n-(29n+20)-15=0
We get rid of parentheses
34n-29n-20-15=0
We add all the numbers together, and all the variables
5n-35=0
We move all terms containing n to the left, all other terms to the right
5n=35
n=35/5
n=7
| -4x+40=48 | | u^2+8u+16+2=29 | | 12x+35+3x+10=180 | | 3+(n/6)=6 | | 78-9p=–51 | | (u+4)^2+2=29 | | 78+-9p=-51 | | m–23=45 | | 2x=7=-15 | | -10=0.5w-7 | | -73+1u=-58 | | –73+1u=–58 | | -10=0.5x-7 | | 30-5x=-15 | | –73––1u=–58 | | 1/5w-3=-7 | | 2. a+4a-9=41 | | 36/d=13 | | 7^3x=20 | | k/19-62=-60 | | 2(4-2x)-2(x+5)=10 | | -17+5u=8 | | (4x-10)+(6x+3)+(5x+7)=180 | | 18260=c | | 19+2n=15 | | 3/4g+2=11 | | 4x=x+188 | | 83b=-4 | | c/5-8=-4 | | n/3-5=1 | | 4(2-3x)+4x=12 | | 15+6j=3 |